Efficacy, immunogenicity and safety of respiratory syncytial virus prefusion F vaccine: systematic review and meta-analysis - Yi Pang; Haishan Lu; Demin Cao; Xiaoying Zhu; Qinqin Long; Fengqin Tian; Xidai Long; Yulei Li (BMC, 2024)
Abstract Objective A notable research gap exists in the systematic review and meta-analysis concerning the efficacy, immunogenicity, and safety of the respiratory syncytial virus (RSV) prefusion F vaccine. Methods We conducted a comprehensive search across PubMed, Embase, the Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov to retrieve articles related to the efficacy, immunogenicity, and safety of RSV prefusion F vaccines, published through September 8, 2023. We adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results A total of 22 randomized controlled trials involving 78,990 participants were included in this systematic review and meta-analysis. The RSV prefusion F vaccine exhibited a vaccine effectiveness of 68% (95% CI: 59-75%) against RSV-associated acute respiratory illness, 70% (95% CI: 60-77%) against medically attended RSV-associated lower respiratory tract illness, and 87% (95% CI: 71-94%) against medically attended severe RSV-associated lower respiratory tract illness. Common reported local adverse reactions following RSV prefusion F vaccination include pain, redness, and swelling at the injection site, and systemic reactions such as fatigue, headache, myalgia, arthralgia, nausea, and chills. Conclusions Our meta-analysis suggests that vaccines using the RSV prefusion F protein as antigen exhibit appears broadly acceptable efficacy, immunogenicity, and safety in the population. In particular, it provides high protective efficiency against severe RSV-associated lower respiratory tract disease.